Impact of Chronic Sleep Deprivation on Blood Pressure Variability and Early Cardiovascular Dysfunction Among Medical Residents: A Clinical Observational Study - Nouman Farooq ,; Ayesha Ghazanfar ,; Uzair Khalid,; Rohma Afzal ,; Haseeb Ahmad, (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Medical residents frequently experience chronic sleep deprivation because of extended duty hours, demanding workloads, and frequent night shifts. Insufficient sleep has been associated with autonomic dysregulation, elevated blood pressure, inflammation, and subclinical cardiac dysfunction, yet limited data exist in young, otherwise healthy physicians. Objective: To assess the impact of chronic sleep deprivation on blood pressure variability (BPV), autonomic function, inflammatory markers, and early echocardiographic indicators of cardiovascular dysfunction among medical residents. Methods: This clinical observational study was conducted from June 2023 to March 2024 at Sheikh Zayed Hospital, Lahore, and Fatima Memorial Hospital, Lahore. A total of 110 medical residents aged 24–35 years were enrolled through consecutive sampling. Participants were divided into a sleep-deprived group (≤6 hours/night; n = 65) and an adequate-sleep group (>6 hours/night; n = 45). Sleep duration was assessed using structured questionnaires and a 7-day sleep diary. All residents underwent office blood pressure measurement, 24-hour ambulatory blood pressure monitoring (ABPM), heart rate variability (HRV) analysis, hs-CRP testing, and transthoracic echocardiography. Results: Sleep-deprived residents exhibited significantly higher 24-hour systolic and diastolic BP, increased BPV, and a greater prevalence of non-dipping patterns. Resting heart rate was elevated, and HRV indices (SDNN and RMSSD) were significantly reduced. hs-CRP levels were higher in the sleep-deprived group, indicating low-grade inflammation. Echocardiographic evaluation showed a significantly higher E/e′ ratio and a greater presence of early diastolic dysfunction. Conclusion: Chronic sleep deprivation adversely affects cardiovascular regulation in medical residents, contributing to increased BPV, autonomic imbalance, inflammation, and early diastolic dysfunction. Structured duty schedules and sleep optimization may reduce these risks.